Estudo longitudinal de lesões profundas de cárie após a remoção incompleta da dentina cariada: 36-45 meses de acompanhamento - Oliveira, Elenara Ferreira de (2006)
This paper assesses clinical/radiographic changes after incomplete carious dentine removal and tooth sealing. 32 teeth with deep caries lesions were studied. The treatment consisted of incomplete excavation, application of Ca (OH)2 layer, sealing for a 6-7 month period, and then restored. Standardized bitewing radiographs were taken after the temporary sealing, and at 6-7, 14-18, and 36-45 month intervals. The digitized images were analyzed: qualitatively in regard to the radiolucent zone (RZ) depth and tertiary dentine (6-7 and 36-45 months) and quantitatively in regard toradiographic density by image subtraction (6-7, 14-18, and 36-45 months). The subtractions were performed in the RZ beneath the restoration and in two control areas (CA). During the 6-7 month period, there was 1 pulp necroses and 1 pulpexposure, and at the 36-45 month interval, 3 fractures and 3 withdrawals. Nine cases showed a decrease in RZ depth in the 6-7 month period and 3 more cases, at the 36- 45 month period. Four cases displayed tertiary dentine. The radiographic density means and standard deviations were: 129.42±5.83, 127.65±4.67, and 126.86±7.03 (CA, P>0.05) and 132.96 ±7.41, 132.90±5.99, and 132.62±8.68 (RZ, P>0.05) for the 1st, 2nd, and 3rd periods. The radiographic density of the CA differed from the RZ (Tukey test, p<0.05). Interference in microbiological metabolism by partial dentine removal and by tooth sealing arrest lesion progression, suggesting that complete dentine caries removal is not essential to controlling caries progression.